Los últimos paracas: fardos funerarios de la tradición Paracas Cavernas de Cerro del Gentil, valle medio de Chincha, costa sur del Perú - Tantaleán, Henry; Gómez Mejía, Juliana; Stanish, Charles (Pontificia Universidad Católica del Perú, 2022)
The funerary practices of the Late Paracas period (500–200 BCE) related to the Cavernas style have been explored at various sites on the southern coast of Peru. However, descriptions of the archaeological contexts where mummy bundles have been recovered are scarce. This work describes nine mummy bundles that were recovered at the site of Cerro del Gentil in the Chincha valley. This article describes the mummification process, describes the objects recovered inside the bundle, and characterizes the biological features of the individuals. The results indicate similarities in the structure and way of preparing the bundles. However, variation in the use of similar objects indicate that people from a wider region participated in the burial practices. The complex spatial arrangement of the objects in these bundles indicates a distinct funerary tradition for the south coast that lasted for several centuries. The findings indicate that the Chincha valley was a central region for the cultural development of the Paracas and that the bundles constituted one of the most important offerings for political and ritual purposes.

Las prácticas funerarias asociadas al periodo Paracas Tardío (500–200 a. C.) relacionadas con el estilo Cavernas han sido exploradas en varios sitios de la costa sur del Perú. Sin embargo, son escasos los contextos arqueológicos donde han sido recuperados fardos funerarios. Este trabajo presenta la descripción y los resultados del análisis realizado a nueve fardos funerarios que fueron recuperados en el sitio Cerro del Gentil, valle de Chincha. El propósito de este artículo es presentar la secuencia de elaboración, describir los elementos recuperados en su interior y caracterizar biológicamente a los individuos. Los resultados indican semejanzas en la estructura y forma de preparación de los fardos. No obstante, objetos similares, pero con variaciones de forma que los hace específicos, indican que personas provenientes de una región más amplia participaron en la elaboración. La complejidad en la distribución de las ofrendas y la conformación de estos fardos revela el desarrollo de una tradición funeraria para la costa sur que perduraría durante varios siglos. Los hallazgos indican que el valle de Chincha fue una región central para el desarrollo cultural de los paracas y que los fardos constituyeron una de las ofrendas más importantes con fines políticos y rituales.
The last paracas: funerary bundles from the Paracas Cavernas tradition at Cerro del Gentil in the middle Chincha valley, south coast of Peru
Keywords: Cerro del Gentil; Chincha; Early Horizon; funerary customs; offerings; mummies; Cerro del Gentil; Chincha; Horizonte Temprano; Prácticas funerarias; Ritual; Ofrendas; Momias; https://purl.org/pe-repo/ocde/ford#6.01.02